# How do you solve 6x-16=68+18x?

May 28, 2017

See below

#### Explanation:

We combine like-terms.

$6 x - 16 = 68 + 18 x$

$- 16 - 68 = 18 x - 6 x$

$- 84 = 12 x$

$- 7 = x$

May 28, 2017

$x = - 7$

See the process in the explanation.

#### Explanation:

Solve:

$6 x - 16 = 68 + 18 x$

Subtract $6 x$ from both sides.

$\textcolor{red}{\cancel{\textcolor{b l a c k}{6 x}}} - \textcolor{red}{\cancel{\textcolor{b l a c k}{6 x}}} - 16 = 68 + 18 x - 6 x$

Simplify.

$- 16 = 68 + 12 x$

Subtract $68$ from both sides.

$- 16 - 68 = \textcolor{red}{\cancel{\textcolor{b l a c k}{68}}} - \textcolor{red}{\cancel{\textcolor{b l a c k}{68}}} + 12 x$

Simplify.

$- 84 = 12 x$

Divide both sides by $12$.

${\textcolor{red}{\cancel{\textcolor{b l a c k}{- 84}}}}^{- 7} / \textcolor{red}{\cancel{\textcolor{b l a c k}{{12}^{1}}}} = \frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{12} \textcolor{b l a c k}{x}}}}{\textcolor{red}{\cancel{\textcolor{b l a c k}{12}}}}$

Simplify.

$- 7 = x$

Switch sides.

$x = - 7$